关于右GP-V-环(On right GP-V-rings) - YANGChun-lan(杨春兰) (Zhejiang Daxue xuebao. Lixue ban, 2009)
GP-V-ring(GP-V-module) is studied which is a generalization of P-V-ring (P-V-module), and the characters are searched for. For example,if R is a right GP-V-ring, then for any maximal subideal K of a principal right ideal U= aR, a ∈R, there exists a maximal right ideal H of R that H ∩anR = K ∩anR , for some n∈Z+；Every principal right ideal of a right GP-V-ring is idempotent,any direct summand of a right GP-V-ring is again a right GP-V-ring and so on. Furthermore, the question when a GP-V-ring is Von Neumann regular is discussed in the remainder.